Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Loyalitas Pasien Rumah Sakit Santa Maria Pekanbaru - Astri Ayu Purwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
In the field of health services that have the task of carrying out a health effort. Hospitals must pay attention to satisfaction for users of their services, namely patients. One way that must be done by the hospital to maintain patients is by providing the best service at the time of sale and when serving patients. The purpose of this study was to find out and analyze the influence of service quality & satisfaction on the loyalty of inpatients of santa maria pekanbaru hospital. The method used is multiple linear regression analysis. The sample used was 100 respondents. The results of this study indicate that tangible and empathy have no significant effect on loyalty while reliability, responsiveness, assurance, and satisfaction have a significant effect on loyalty. Keywords : Tangible,Reliability,Responsiveness,Assurance,Empathy, Significant,Loyalty